The Role of Type 2 Innate Lymphoid Cells in Allergic Diseases - Zheng, Haocheng; Zhang, Yi; Pan, Jiachuang; Liu, Nannan; Qin, Yu; Qiu, Linghui; Liu, Min; Wang, Tieshan (Frontiers in Immunology, 2021)
Allergic diseases have been significant diseases that plague many patients around the world. In the past few decades, with environmental changes and social development, the incidence of allergic diseases has increased significantly, which has caused a huge burden on public health and even led to premature death. In the study of allergic diseases, the understanding of the mechanism of allergic diseases has made a lot of progress, and it has been found that the occurrence of allergic diseases and changes in the immune system state is inseparable. With the identification and in-depth understanding of innate lymphoid cells, researchers have gradually understood that type 2 innate lymphoid cells(ILC2s) have an important role in many allergic diseases. ILC2-mediated type 2 immune response may be the cause of some of the special phenomena which have been found in the past in the occurrence of allergic diseases. However, our current studies of ILC2s are limited, and their status in allergic diseases is still not entirely clear. This article provides an overview of the common phenotypes, the activation pathways, and the potential research field of ILC2s in different allergic diseases, to promote the further understanding of the role of ILC2s in different allergic diseases, and ultimately find the new treatment for these diseases.